Principal Leadership Strategies for Enhancing Student Self-Confidence Through Assembly Programs - Ainul Yaqin, Muhammad; Fadilah, Nurul; Vorfi Lama, Alma (At-Tarbiyat, 2025)
This research aims to analyze the principal's strategy in implementing the Assembly program to increase students' self-confidence at Bhakti Pertiwi Middle School. The Assembly Program functions as a forum for students to practice public speaking, grow courage, and build self-confident character. However, the implementation of this program still faces various obstacles, such as minimal student participation and lack of support from the school environment. The research method used is a descriptive qualitative approach with data collection techniques through interviews, observation and documentation. Research subjects included school principals, teachers and students involved in the Majlis program. Data were analyzed using data reduction techniques, data presentation, and drawing conclusions. The research results show that the principal's strategy in optimizing the Majlis program includes preparing supportive school policies, providing motivation to students, involving teachers as facilitators, and creating a conducive environment. This program has proven to be effective in increasing students' self-confidence, especially through an experience-based and habituation approach. The implications of this research emphasize the importance of school principal leadership in designing innovative and sustainable strategies to build student character. These findings can be a reference for other schools in implementing similar programs to improve the quality of education.